2020
DOI: 10.3389/fmars.2019.00826
|View full text |Cite
|
Sign up to set email alerts
|

The Azores: A Mid-Atlantic Hotspot for Marine Megafauna Research and Conservation

Abstract: The increasing public perception that marine megafauna is under threat is an outstanding incentive to investigate their essential habitats (EMH), their responses to human and climate change pressures, and to better understand their largely unexplained behaviors and physiology. Yet, this poses serious challenges such as the elusiveness and remoteness of marine megafauna, the growing scrutiny and legal impositions on their study, and difficulties in disentangling environmental drivers from human disturbance. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…We focused on the putative nurseries along the north coast of Faial Island, but the adopted multi-scale approach spans the neighboring island of Pico (the two islands being separated only by a shallow 9-km-wide channel), the chain of seamounts close to the two islands, and, eventually, the whole archipelago. The islands' coastal habitats are greatly influenced by the region's ecotone position and dominant oceanographic regime whereby the southern branch of the warm Gulf Current, which passes south of the islands, and its eddies and filaments promote a dynamic sub-tropical influence on its warmtemperate general character (Santos et al, 1995;Afonso et al, 2020). The shelves of the islands are very narrow, typically dropping from the shore to the break (at ca.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the putative nurseries along the north coast of Faial Island, but the adopted multi-scale approach spans the neighboring island of Pico (the two islands being separated only by a shallow 9-km-wide channel), the chain of seamounts close to the two islands, and, eventually, the whole archipelago. The islands' coastal habitats are greatly influenced by the region's ecotone position and dominant oceanographic regime whereby the southern branch of the warm Gulf Current, which passes south of the islands, and its eddies and filaments promote a dynamic sub-tropical influence on its warmtemperate general character (Santos et al, 1995;Afonso et al, 2020). The shelves of the islands are very narrow, typically dropping from the shore to the break (at ca.…”
Section: Study Areamentioning
confidence: 99%
“…Finally, these putative EFHs may also play a role of greater importance to the north Atlantic smooth hammerhead population(s) the juveniles (and pupping females) belong to. For example, it is very possible that the oceanic adults and preadults in the tropical north-east Atlantic were born at nurseries located in the Azores and other oceanic islands (Afonso et al, 2020), and that females return to these nurseries to pup later in life via philopatric behavior, as seems to be the case in the Northern Mexican Pacific (Feĺix-Loṕez et al, 2019). In this case, oceanic island nurseries/EFH should explicitly be put in context with other (adult) EFH, including the pupping migrating corridors, in current international fisheries management approaches as implemented by the international bodies (e.g., ICAAT, CBD, and OSPAR).…”
Section: Function Of the Nurseries And Management Implicationsmentioning
confidence: 99%
“…Cetaceans are a highly charismatic marine megafauna group whose research and conservation presents numerous challenges (e.g. high mobility and amount of time spent below the surface, low detectability and difficulties associated with their identification, large distribution and seasonal migrations of some species, high economic costs of undertaking assessment studies and difficulty in accessing thier oceanic habitats; Mann, 1999; Redfern et al, 2006; Kaschner et al, 2012; Horton et al, 2017; Thums et al, 2018; Afonso et al, 2020). The study of their movement patterns is not only essential for understanding population ecology and biogeographical patterns, but also to assess the conservation status of populations across their entire home range, and evaluate the extent to which they are subjected to increasing anthropogenic impacts (Whitehead, 2001; Sequeira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At-sea surveys are rare for southeast Greenland, but multi-colony studies have shown that the area is rarely used by seabirds during this period (e.g., black-legged kittiwake Rissa tridactyla [57], thick-billed murre Uria lomvia [42], little auk Alle alle [79], Atlantic puffin [47]). In contrast, female puffins traveled farther south and utilized Canadian conservation areas and ecologically and biologically significant marine areas (EBSA) of the western North Atlantic and marine protected areas (MPA) of the high seas along the mid-Atlantic, areas known to have large numbers of wintering seabirds [80][81][82][83].…”
Section: Use Areas Of Geographic Importancementioning
confidence: 99%